Platelet-rich Plasma and Its Application in Clinical Trial - Thi Thanh, Pham; Mai, Nguyen Thi; Ha, Nguyen Thi Ngoc; Hien, Mai Thi; Tu, Nguyen Dac (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
Platelet-rich plasma (PRP) is an autologous physiological product that has a platelet concentration above baseline. The PRP contains a high level of important growth factors and cytokines such as PDGF, EGF, VEGF, TGF-β,... which play important roles in healing and tissue regeneration. The PRP is currently used in various medical fields, including orthopedic, plastic surgery, dermatology, dentistry, musculoskeletal and obstetrics-gynecology. To date, the results from in vitro , in vivo studies to clinical trials have proved the effectiveness of PRP in the treating of many diseases. Altogether, PRP is considered to be a very promising futuristic therapy by dint of its simple and highly potential clinical application. Keywords: Platelet-rich plasma, PRP, growth factors, applications of platelet-rich plasma. References [1] J. S. F. Moure, J. L. V. Eps, F. J. Cabrera, Z. Barbosa, G. M. D. Rosal, B. K. Weiner, et al., Platelet-rich Plasma: A Biomimetic Approach to Enhancement of Surgical Wound Healing, Journal of Surgical Research, Vol. 207, No., 2017, pp. 33-44, https://doi.org/10.1016/j.jss.2016.08.063. [2] A. Zarbock, R. K. P. Grabowska, K. Ley, Platelet-neutrophil-interactions: Linking Hemostasis and Inflammation, Blood Reviews, Vol. 21, No. 2, 2007, pp. 99-111, https://doi.org/10.1016/j.blre.2006.06.001. [3] R. E. Marx, Platelet-rich Plasma (PRP): what is PRP and what is not PRP?, Implant Dentistry, Vol. 10, No. 4, 2001, pp. 225-228, https://doi.org/10.1097/00008505-200110000-00002. [4] R. Alves, R. Grimalt, A Review of Platelet-Rich Plasma: History, Biology, Mechanism of Action, and Classification, Skin Appendage Disord, Vol. 4, No. 1, 2018, pp. 18-24, https://doi.org/10.1159/000477353. [5] P. A. Everts, J. T. Knape, G. Weibrich, J. P. Schonberger, J. Hoffmann, E. P. Overdevestet al., Platelet-rich Plasma and Platelet Gel: A Review, The Journal of ExtraCorporeal Technology, Vol. 38, No. 2, 2006, pp. 174-187. [6] A. Mishra, J. W. Jr, A. Vieira, Treatment of Tendon and Muscle Using Platelet-rich Plasma, Clinics in Sports Medicine, Vol. 28, No. 1, 2009, pp. 113-125, https://doi.org/10.1016/j.csm.2008.08.007. [7] R. Dhurat, M. Sukesh, Principles and Methods of Preparation of Platelet-rich Plasma: A Review and Author's Perspective, Journal of Cutaneous Aesthetic Surgery, Vol. 7, No. 4, 2014, pp. 189-197, https://doi.org/10.4103/0974-2077.150734. [8] B. L. Eppley, W. S. Pietrzak, M. Blanton, Platelet-rich Plasma: A Review of Biology and Applications in Plastic Surgery, Plastic and Reconstructive Surgery, Vol. 118, No. 6, 2006, pp. 147e-159e, https://doi.org/10.1097/01.prs.0000239606.92676.cf. [9] K. Mautner, G. Malanga, R. Colberg, Optimization of Ingredients, Procedures and Rehabilitation for Platelet-rich Plasma Injections for Chronic Tendinopathy, Pain Management, Vol. 1, No. 6, 2011, pp. 523-532, https://doi.org/10.2217/pmt.11.56. [10] C. Kia, J. Baldino, R. Bell, A. Ramji, C. Uyeki, A. Mazzocca, Platelet-rich Plasma: Review of Current Literature on its Use for Tendon and Ligament Pathology, Current Reviews in Musculoskeletal Medicine, Vol. 11, No. 4, 2018, pp. 566-572, https://doi.org/10.1007/s12178-018-9515-y. [11] J. Alsousou, M. Thompson, P. Hulley, A. Noble, K. Willett, The Biology of Platelet-rich Plasma and its Application in Trauma and Orthopaedic Surgery: A Review of The Literature, The Journal of Bone and Joint Surgery British volume, Vol. 91, No. 8, 2009, pp. 987-996, https://doi.org/10.1302/0301-620X.91B8.22546. [12] W. J. Berghoff, W. S. Pietrzak, R. D. Rhodes, Platelet-rich Plasma Application During Closure Following Total Knee Arthroplasty, Orthopedics, Vol. 29, No. 7, 2006, pp. 590-598, https://doi.org/10.3928/01477447-20060701-11. [13] D. R. Knighton, K. F. Ciresi, V. D. Fiegel, L. L. Austin, E. L. Butler, Classification and Treatment of Chronic Nonhealing Wounds. Successful Treatment with Autologous Platelet-derived Wound Healing Factors (PDWHF), Annals of Surgery, Vol. 204, No. 3, 1986, pp. 322-330, https://doi.org/10.1097/00000658-198609000-00011. [14] N. N. Tuan, N. T. Dung, Studying the Effects of Platelet-rich Plasma and Adipose Tissue-derived Stem cells on Chronic Wound Treatment, Journal of Disaster Medicine and Burn Injuries, Vol. 5, 2018 (in Vietnamese). [15] D. M. Dohan Ehrenfest, T. Bielecki, A. Mishra, P. Borzini, F. Inchingolo, G. Sammartino et al., in Search of A Consensus Terminology in The Field of Platelet Concentrates for Surgical Use: Platelet-rich Plasma (PRP), Platelet-rich Fibrin (PRF), Fibrin Gel Polymerization and Leukocytes, Current Pharmaceutical Biotechnology, Vol. 13, No. 7, 2012, pp. 1131-1137, https://doi.org/10.2174/138920112800624328. [16] D. H. Whitman, R. L. Berry, D. M. Green, Platelet Gel: An Autologous Alternative to Fibrin Glue with Applications in Oral and Maxillofacial Surgery, Journal of Oral Maxillofacial Surgery, Vol. 55, No. 11, 1997, pp. 1294-1299, https://doi.org/10.1016/s0278-2391(97)90187-7. [17] P. A. Mooar, M. J. Gardner, P. R. Klepchick, The Efficacy of Autologous Platelet Gel in Total Knee Arthroplasty: An Analysis of Range of Motion, Hemoblobin, and Narcotic Requirements, In: 67th Annual Meeting. American Academy of Orthopaedic Surgeons, 2000. [18] T. M. Bielecki, T. S. Gazdzik, J. Arendt, T. Szczepanski, W. Krol, T. Wielkoszynski, Antibacterial Effect of Autologous Platelet Gel Enriched with Growth Factors and Other Active Substances: An in Vitro Study, The Journal of Bone and Joint Surgery British volume, Vol. 89, No. 3, 2007, pp. 417-420, https://doi.org/10.1302/0301-620X.89B3.18491. [19] D. J. Moojen, P. A. Everts, R. M. Schure, E. P. Overdevest, A. V. Zundert, J. T. Knape et al., Antimicrobial Activity of Platelet-leukocyte Gel Against Staphylococcus Aureus, Journal of Orthopaedic Research, Vol. 26, No. 3, 2008, pp. 404-410, https://doi.org/10.1002/jor.20519. [20] D. M. D. Ehrenfest, L. Rasmusson, T. Albrektsson, Classification of Platelet Concentrates: from Pure Platelet-rich Plasma (P-PRP) to Leucocyte- and Platelet-rich Fibrin (L-PRF), Trends in Biotechnology, Vol. 27, No. 3, 2009, pp. 158-167, https://doi.org/10.1016/j.tibtech.2008.11.009. [21] R. E. Marx, E. R. Carlson, R. M. Eichstaedt, S. R. Schimmele, J. E. Strauss, K. R. Georgeff, Platelet-rich Plasma: Growth Factor Enhancement for Bone Grafts, Oral Surgery Oral Medicine Oral Pathology Oral Radiology, Vol. 85, No. 6, 1998, pp. 638-646, https://doi.org/10.1016/s1079-2104(98)90029-4. [22] R. Alissa, M. Esposito, K. Horner, R. Oliver, The Influence of Platelet-rich Plasma on The Healing of Extraction Sockets: An Explorative Randomised Clinical Trial, European Journal of Oral Implantology, Vol. 3, No. 2, 2010, pp. 121-134. [23] R. C. Mariano, W. M. D. Melo, C. C. Avelino, Comparative Radiographic Evaluation of Alveolar Bone Healing Associated with Autologous Platelet-rich Plasma After Impacted Mandibular Third Molar Surgery, Journal of Oral and Maxillofacial Surgery, Vol. 70, No. 1, 2012, pp. 19-24, https://doi.org/10.1016/j.joms.2011.03.028. [24] C. Bacci, M. Maglione, L. Favero, A. Perini, R. D. Lenarda, M. Berengo et al., Management of Dental Extraction in Patients Undergoing Anticoagulant Treatment. Results From A Large, Multicentre, Prospective, Case-control Study, Journal of Thrombosis and Haemostasis, Vol. 104, No. 5, 2010, pp. 972-975, https://doi.org/10.1160/TH10-02-0139. [25] E. Anitua, M. Sanchez, A. T. Nurden, M. Zalduendo, M. D. L. Fuente, J. Azofra et al., Reciprocal Actions of Platelet-secreted TGF-beta1 on The Production of VEGF and HGF by Human Tendon Cells, Plastic and Reconstructive Surgery, Vol. 119, No. 3, 2007, pp. 950-959, https://doi.org/10.1097/01.prs.0000255543.43695.1d. [26] B. O'Connell, N. M. Wragg, S. L. Wilson, The Use of PRP Injections in The Management of Knee Osteoarthritis, Cell and Tissue Research, Vol. 376, No. 2, 2019, pp. 143-152, https://doi.org/10.1007/s00441-019-02996-x. [27] M. A. S. Mendia, J. F. V. Cavazos, H. G. M. Rodriguez, Platelet-rich Plasma in Knee Osteoarthritis Treatment, Cirugia y Cirujanos, Vol. 83, No. 4, 2015, pp. 352-358, https://doi.org/10.1016/j.circir.2014.06.001. [28] H. H. E. Hadmed, R. F. Castillo, Cosmeceuticals: Peptides, Proteins, and Growth Factors, Journal of Cosmetic Dermatology, Vol. 15, No. 4, 2016, pp. 514-519, https://doi.org/10.1111/jocd.12229. [29] D. H. Kim, Y. J. Je, C. D. Kim, Y. H. Lee, Y. J. Seo, J. H. Lee et al., Can Platelet-rich Plasma Be Used for Skin Rejuvenation? Evaluation of Effects of Platelet-rich Plasma on Human Dermal Fibroblast, Annals of Dermatology, Vol. 23, No. 4, 2011, pp. 424-431, https://doi.org/10.5021/ad.2011.23.4.424. [30] N. Cameli, M. Mariano, I. Cordone, E. Abril, S. Masi, M. L. Foddai, Autologous Pure Platelet-Rich Plasma Dermal Injections for Facial Skin Rejuvenation: Clinical, Instrumental, and Flow Cytometry Assessment, Dermatologic Surgery, Vol. 43, No. 6, 2017, pp. 826-835, https://doi.org/10.1097/DSS.0000000000001083. [31] O. K. Abuaf, H. Yildiz, H. Baloglu, M. E. Bilgili, H. A. Simsek, B. Dogan, Histologic Evidence of New Collagen Formulation Using Platelet Rich Plasma in Skin Rejuvenation: A Prospective Controlled Clinical Study, Annals of Dermatology, Vol. 28, No. 6, 2016, pp. 718-724, https://doi.org/10.5021/ad.2016.28.6.718. [32] N. Y. Elnehrawy, Z. A. Ibrahim, A. M. Eltoukhy, H. M. Nagy, Assessment of the Efficacy and Safety of Single Platelet-rich Plasma Injection on Different Types and Grades of Facial Wrinkles, Journal of Cosmetic Dermatology, Vol. 16, No. 1, 2017, pp. 103-111, https://doi.org/10.1111/jocd.12258. [33] B. Hersant, M. S. Mezi, J. Niddam, S. L. Padula, W. Noel, K. Ezzedine et al., Efficacy of Autologous Platelet-rich Plasma Combined with Hyaluronic Acid on Skin Facial Rejuvenation: A Prospective Study, Journal of the American Academy of Dermatology, Vol. 77, No. 3, 2017, pp. 584-586, https://doi.org/10.1016/j.jaad.2017.05.022. [34] Z. A. Ibrahim, R. A. E. Tatawy, M. A. E. Samongy, D. A. Ali, Comparison Between The Efficacy and Safety of Platelet-rich Plasma vs. Microdermabrasion in the Treatment of Striae Distensae: Clinical and Histopathological Study, Journal of Cosmetic Dermatology, Vol. 14, No. 4, 2015, pp. 336-346, https://doi.org/10.1111/jocd.12160. [35] A. Tuknayat, G. P. Thami, M. Bhalla, J. K. Sandhu, Autologous Intralesional Platelet-rich Plasma Improves Melasma, Dermatologic Therapy, Vol. 34, No. 2, 2021, pp. e14881, https://doi.org/10.1111/dth.14881. [36] V. Cervelli, F. Nicoli, D. Spallone, S. Verardi, R. Sorge, M. Nicoli et al., Treatment of Traumatic Scars Using Fat Grafts Mixed with Platelet-rich Plasma, and Resurfacing of Skin with The 1540 nm Nonablative Laser, Clinical and Experimental Dermatology, Vol. 37, No. 1, 2012, pp. 55-61, https://doi.org/10.1111/j.13652230.2011.04199.x. [37] A. C. Nita, O. A. Orzan, M. Filipescu, D. Jianu, Fat Graft, Laser CO(2) and Platelet-rich Plasma Synergy in Scars Treatment, Journal of Medicine and Life, Vol. 6, No. 4, 2013, pp. 430-433. [38] R. James, R. Chetry, V. Subramanian, A. Ashtekar, N. Srikruthi, S. Ramachandran et al., Efficacy of Activated 3X Platelet-Rich Plasma in the Treatment of Androgenic Alopecia, Journal of Stem Cells, Vol. 11, No. 4, 2016, pp. 191-199. [39] R. Alves, R. Grimalt, Randomized Placebo-Controlled, Double-Blind, Half-Head Study to Assess the Efficacy of Platelet-rich Plasma on the Treatment of Androgenetic Alopecia, Dermatologic Surgery, Vol. 42, No. 4, 2016, pp. 491-497, https://doi.org/10.1097/DSS.0000000000000665. [40] C. E. Finch, The Menopause and Aging, A Comparative Perspective, The Journal of Steroid Biochemistry and Molecular Biology, Vol. 142, No., 2014, pp. 132-141, https://doi.org/10.1016/j.jsbmb.2013.03.010. [41] Y. Chang, J. Li, Y. Chen, L. Wei, X. Yang, Y. Shi et al., Autologous Platelet-rich Plasma Promotes Endometrial Growth and Improves Pregnancy Outcome During In Vitro Fertilization, International Journal of Clinical and Experimental Medicine, Vol. 8, No. 1, 2015, pp. 1286-1290. [42] S. Zadehmodarres, S. Salehpour, N. Saharkhiz, L. Nazari, Treatment of Thin Endometrium with Autologous Platelet-rich Plasma: A Pilot Study, JBRA Assisted Reproduction, Vol. 21, No. 1, 2017, pp. 54-56, https://doi.org/10.5935/1518-0557.20170013. [43] Y. Chang, J. Li, L. N. Wei, J. Pang, J. Chen, X. Liang, Autologous Platelet-rich Plasma Infusion Improves Clinical Pregnancy Rate in Frozen Embryo Transfer Cycles for Women with Thin Endometrium, Medicine (Baltimore), Vol. 98, No. 3, 2019, https://doi.org/10.1097/MD.0000000000014062. [44] S. R. Tandulwadkar, M. V. Naralkar, A. D. Surana, M. Selvakarthick, A. H. Kharat, Autologous Intrauterine Platelet-Rich Plasma Instillation for Suboptimal Endometrium in Frozen Embryo Transfer Cycles: A Pilot Study, Journal of Human Reproductive Sciences, Vol. 10, No. 3, 2017, pp. 208-212, https://doi.org/10.4103/jhrs.JHRS_28_17. [45] A. Molina, J. Sanchez, W. Sanchez, V. Vielma, Platelet-rich Plasma As An Adjuvant in the Endometrial Preparation of Patients with Refractory Endometrium, JBRA Assisted Reproduction, Vol. 22, No. 1, 2018, pp. 42-48, https://doi.org/10.5935/1518-0557.20180009. [46] K. Pantos, N. Nitsos, G. Kokkali, T. Vaxevanoglou, C. Markomichali, A. Pantou, Ovarian Rejuvenation and Folliculogenesis Reactivation in Peri-menopausal Women After Autologous Platelet-rich Plasma Treatment, in Proceedings of the 32nd Annual Meeting of ESHRE, Helsinki, Finland, 2016. [47] K. Pantos, M. Simopoulou, A. Pantou, A. Rapani, P. Tsioulou, N. Nitsos, et al., A Case Series on Natural Conceptions Resulting in Ongoing Pregnancies in Menopausal and Prematurely Menopausal Women Following Platelet-rich Plasma Treatment, Cell Transplant, Vol. 28, No. 9-10, 2019, pp. 1333-1340, https://doi.org/10.1177/0963689719859539. [48] J. Fanning, L. Murrain, R. Flora, T. Hutchings, J. M. Johnson, B. W. Fenton, Phase I/II Prospective Trial of Autologous Platelet Tissue Graft in Gynecologic Surgery, Journal of Minimally Invasive Gynecology, Vol. 14, No. 5, 2007, pp. 633-637, https://doi.org/10.1016/j.jmig.2007.05.014. [49] X. Hua, Y. Zeng, R. Zhang, H. Wang, J. Diao, P. Zhang, Using Platelet-rich Plasma for the Treatment of Symptomatic Cervical Ectopy, International Journal of Gynaecology & Obstetrics, Vol. 119, No. 1, 2012, pp. 26-29, https://doi.org/10.1016/j.ijgo.2012.05.029. [50] F. B. Willison, N. R. Pour, B. Mohamadi, N. Willison, M. Rock, I. W. Holten et al., Use of Platelet-rich Plasma for Vulvovaginal Autoimmune Conditions Like Lichen Sclerosus, Plastic and Reconstructive Surgery Global Open, Vol. 4, No. 11, 2016, pp. e1124, https://doi.org/10.1097/GOX.0000000000001124. [51] M. Morelli, M. L. Rocca, R. Venturella, A. D. Cello, S. D. Negro, M. Condorelli et al., Adjuvant Use of Platelet Gel for Wound Breakdown Prevention in Advanced Vulvar Cancer Surgery: A Retrospective Study, International Journal of Gynecological Cancer, Vol. 23, No. 8, 2013, pp. 1490-1494, https://doi.org/10.1097/IGC.0b013e3182a50517. [52] B. B. Adler, E. Hanzal, E. Pablik, H. Koelbl, K. Bodner, Management of Vesicovaginal Fistulas (VVFs) in Women Following Benign Gynaecologic Surgery: A Systematic Review and Meta-analysis, PLoS One, Vol. 12, No. 2, 2017, pp. e0171554, https://doi.org/10.1371/journal.pone.0171554. [53] A. S. Plachokova, J. V. D. Dolder, P. J. Stoelinga, J. A. Jansen, The Bone Regenerative Effect of Platelet-rich Plasma in Combination with An Osteoconductive Material in Rat Cranial Defects, Clinical Oral Implants Research, Vol. 17, No. 3, 2006, pp. 305-311, https://doi.org/10.1111/j.1600-0501.2005.01208.x. [54] A. S. Plachokova, J. V. D. Dolder, P. J. Stoelinga, J. A. Jansen, Early Effect of Platelet-rich Plasma on Bone Healing in Combination with An Osteoconductive Material in Rat Cranial Defects, Clinical Oral Implants Research, Vol. 18, No. 2, 2007, pp. 244-251, https://doi.org/10.1111/j.1600-0501.2006.01327.x. [55] B. H. Choi, C. J. Im, J. Y. Huh, J. J. Suh, S. H. Lee, Effect of Platelet-rich Plasma on Bone Regeneration in Autogenous Bone Graft, International Journal of Oral Maxillofacial Surgery, Vol. 33, No. 1, 2004, pp. 56-59, https://doi.org/10.1054/ijom.2003.0466. [56] B. L. Walters, D. A. Porter, S. J. Hobart, B. B. Bedford, D. E. Hogan, M. M. McHugh et al., Effect of Intraoperative Platelet-Rich Plasma Treatment on Postoperative Donor Site Knee Pain in Patellar Tendon Autograft Anterior Cruciate Ligament Reconstruction: A Double-Blind Randomized Controlled Trial, The American Journal of Sports Medicine, Vol. 46, No. 8, 2018, pp. 1827-1835, https://doi.org/10.1177/0363546518769295. [57] G. E. Niazi, M. S. Hassan, D. M. Elfawy, Ultrasound-guided Injection of Platelet-rich Plasma (PRP) in Rotator Cuff Tendinopathy: Effect on Patients’ Symptoms and Supraspinatus Tendon Thickness, Egyptian Journal of Radiology and Nuclear Medicine, Vol. 51, No. 1, 2020, https://doi.org/ 10.1186/s43055-020-00221-2. [58] L. D. Sante, C. Villani, V. Santilli, M. Valeo, E. Bologna, L. Imparato et al., Intra-articular Hyaluronic Acid vs Platelet-rich Plasma in the Treatment of Hip Osteoarthritis, Medical Ultrasonography, Vol. 18, No. 4, 2016, pp. 463-468, https://doi.org/10.11152/mu-874. [59] J. Wiltfang, K. A. Schlegel, S. S. Mosgau, E. Nkenke, R. Zimmermann, P. Kessler, Sinus Floor Augmentation with Beta-tricalciumphosphate (beta-TCP): Does Platelet-rich Plasma Promote its Osseous Integration and Degradation?, Clinical Oral Implants Research, Vol. 14, No. 2, 2003, pp. 213-218, https://doi.org/10.1034/j.16000501.2003.140212.x. [60] J. H. Wang, X. Nirmala, Application of Tendon Stem/Progenitor Cells and Platelet-Rich Plasma to Treat Tendon Injuries, Operative Techniques in Orthopaedics, Vol. 26, No. 2, 2016, pp. 68-72, https://doi.org/10.1053/j.oto.2015.12.008. [61] H. Toumi, T. M. Best, The Inflammatory Response: Friend or Enemy for Muscle Injury?, British Journal of Sports Medicine, Vol. 37, No. 4, 2003, pp. 284-286, https://doi.org/10.1136/bjsm.37.4.284. [62] C. Smith, M. J. Kruger, R. M. Smith, K. H. Myburgh, The Inflammatory Response to Skeletal Muscle Injury: Illuminating Complexities, Sports Medicine, Vol. 38, No. 11, 2008, pp. 947-969, https://doi.org/10.2165/00007256-200838110-00005.